Gene expression polymorphism underpins evasion of host immunity in an asexual lineage of the Irish potato famine pathogen - Marina Pais; Kentaro Yoshida; Artemis Giannakopoulou; Mathieu A. Pel; Liliana M. Cano; Ricardo F. Oliva; Kamil Witek; Hannele Lindqvist-Kreuze; Vivianne G. A. A. Vleeshouwers; Sophien Kamoun (BMC Evolutionary Biology, 2018)
Abstract Background Outbreaks caused by asexual lineages of fungal and oomycete pathogens are a continuing threat to crops, wild animals and natural ecosystems (Fisher MC, Henk DA, Briggs CJ, Brownstein JS, Madoff LC, McCraw SL, Gurr SJ, Nature 484:186–194, 2012; Kupferschmidt K, Science 337:636–638, 2012). However, the mechanisms underlying genome evolution and phenotypic plasticity in asexual eukaryotic microbes remain poorly understood (Seidl MF, Thomma BP, BioEssays 36:335–345, 2014). Ever since the 19th century Irish famine, the oomycete Phytophthora infestans has caused recurrent outbreaks on potato and tomato crops that have been primarily caused by the successive rise and migration of pandemic asexual lineages (Goodwin SB, Cohen BA, Fry WE, Proc Natl Acad Sci USA 91:11591–11595, 1994; Yoshida K, Burbano HA, Krause J, Thines M, Weigel D, Kamoun S, PLoS Pathog 10:e1004028, 2014; Yoshida K, Schuenemann VJ, Cano LM, Pais M, Mishra B, Sharma R, Lanz C, Martin FN, Kamoun S, Krause J, et al. eLife 2:e00731, 2013; Cooke DEL, Cano LM, Raffaele S, Bain RA, Cooke LR, Etherington GJ, Deahl KL, Farrer RA, Gilroy EM, Goss EM, et al. PLoS Pathog 8:e1002940, 2012). However, the dynamics of genome evolution within these clonal lineages have not been determined. The objective of this study was to use a comparative genomics and transcriptomics approach to determine the molecular mechanisms that underpin phenotypic variation within a clonal lineage of P. infestans. Results Here, we reveal patterns of genomic and gene expression variation within a P. infestans asexual lineage by comparing strains belonging to the South American EC-1 clone that has dominated Andean populations since the 1990s (Yoshida K, Burbano HA, Krause J, Thines M, Weigel D, Kamoun S, PLoS Pathog 10e1004028, 2014; Yoshida K, Schuenemann VJ, Cano LM, Pais M, Mishra B, Sharma R, Lanz C, Martin FN, Kamoun S, Krause J, et al. eLife 2:e00731, 2013; Delgado RA, Monteros-Altamirano AR, Li Y, Visser RGF, van der Lee TAJ, Vosman B, Plant Pathol 62:1081–1088, 2013; Forbes GA, Escobar XC, Ayala CC, Revelo J, Ordonez ME, Fry BA, Doucett K, Fry WE, Phytopathology 87:375–380, 1997; Oyarzun PJ, Pozo A, Ordonez ME, Doucett K, Forbes GA, Phytopathology 88:265–271, 1998). We detected numerous examples of structural variation, nucleotide polymorphisms and loss of heterozygosity within the EC-1 clone. Remarkably, 17 genes are not expressed in one of the two EC-1 isolates despite apparent absence of sequence polymorphisms. Among these, silencing of an effector gene was associated with evasion of disease resistance conferred by a potato immune receptor. Conclusions Our findings highlight the molecular changes underpinning the exceptional genetic and phenotypic plasticity associated with host adaptation in a pandemic clonal lineage of a eukaryotic plant pathogen. We observed that the asexual P. infestans lineage EC-1 can exhibit phenotypic plasticity in the absence of apparent genetic mutations resulting in virulence on a potato carrying the Rpi-vnt1.1 gene. Such variant alleles may be epialleles that arose through epigenetic changes in the underlying genes.